2019
DOI: 10.1002/hed.25830
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of miRNA‐181a with phase angle derived from bioelectrical impedance predicts radiotherapy‐induced changes in body composition and survival of male patients with head and neck cancer

Abstract: Background Nutritional deficits developing as an effect of applied radiotherapy (RTH) negatively affect patients' quality of life, survival, and therapy outcomes. We demonstrated novel approach to prediction of RTH‐induced changes in body composition of patients with head and neck cancer using phase angle (PA) derived from bioelectrical impedance in combination with miRNA‐181a expression. Results Patients with simultaneous presence of low PA and high miRNA expression were at a significantly higher risk of decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Phase angle ( R = .516, p < .01), BMI ( R = .466, p < .01), and waist circumference ( R = .889, p < .01) were positively correlated with MAC, while albumin ( R = −.426, p < .01) and EW/TBW ( R = −0.357, p < .004) were negatively correlated with MAC, respectively (Krishnamoorthy et al., 2015; Tan et al., 2019). Considering M‐BIA as predictor in the evaluation of health in populations (Norman et al., 2012; Powrózek et al., 2019; Vermeulen, Lopes, Alves et al., 2019), our result also indicated that PA can be used as independent factor associated with malnutrition in CKD patients.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Phase angle ( R = .516, p < .01), BMI ( R = .466, p < .01), and waist circumference ( R = .889, p < .01) were positively correlated with MAC, while albumin ( R = −.426, p < .01) and EW/TBW ( R = −0.357, p < .004) were negatively correlated with MAC, respectively (Krishnamoorthy et al., 2015; Tan et al., 2019). Considering M‐BIA as predictor in the evaluation of health in populations (Norman et al., 2012; Powrózek et al., 2019; Vermeulen, Lopes, Alves et al., 2019), our result also indicated that PA can be used as independent factor associated with malnutrition in CKD patients.…”
Section: Discussionsupporting
confidence: 56%
“…Considering M-BIA as predictor in the evaluation of health in populations (Norman et al, 2012;Powrózek et al, 2019;, our result also indicated that PA can be used as independent factor associated with malnutrition in CKD patients. Karavetian et al (2019)…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The high level of miR-181a expression along with a low value of the phase angle (PA) was associated with a higher risk of reducing FFM parameters (OR = 4.72; p = 0.04) and FFMI (OR = 3.21; p = 0.04). Moreover, patients with low PA and high expression of the studied miRNA had shorter OS (HR = 3.18; 95% Cl = 1.19-8.50; p = 0.002) [52].…”
Section: Discussionmentioning
confidence: 90%
“…The presence of the A allele of the ITGAM significantly (over 14-fold) reduced the risk of severe disturbances in nutritional status assessed according to the SGA scale (OR = 0.07) during RT miRNA-130a [78] Patients with low miRNA expression had over a three-fold higher risk of BMI decrease below 18.5, over six-fold higher risk of losing over 5% of body weight, and higher risk of > 10% weight reduction OR = 14.18, after the RT miRNA-181a + PA [107] Patients with simultaneous presence of low PA and high miRNA expression were at a significantly higher risk of decreasing the FFMI < 14.9 kg/m 2 (OR = 5.14), FFM < 44.7 kg (OR = 6.20), and lean mass (OR = 10.0) during RT Elevations in inflammatory cytokines and impairments in leptin/ghrelin functioning are associated with symptoms of cancer cachexia. Moreover, leptin level can decrease after the commencement of RT [108].…”
Section: Itgam-323g>a [106]mentioning
confidence: 99%